Unidirectional orbital magnetoresistance in light-metal–ferromagnet bilayers - Shilei Ding; Paul Noël; Gunasheel Kauwtilyaa Krishnaswamy; Pietro Gambardella (Physical Review Research, 2022)
We report the observation of a unidirectional magnetoresistance (UMR) that originates from the nonequilibrium orbital momentum induced by an electric current in a naturally oxidized Cu/Co bilayer. The orbital UMR scales with the torque efficiency due to the orbital Rashba-Edelstein effect upon changing the Co thickness and temperature, reflecting their common origin. We attribute the UMR to orbital-dependent electron scattering and orbital to spin conversion in the ferromagnetic layer. In contrast to the spin current induced UMR, the magnon contribution to the orbital UMR is absent in thin Co layers, which we ascribe to the lack of coupling between low-energy magnons and orbital current. The magnon contribution to the UMR emerges in Co layers thicker than about 5 nm, which is comparable to the orbital to spin conversion length. Our results provide insight into orbital- to spin-momentum transfer processes relevant for the optimization of spintronic devices based on light metals and orbital transport.